Analysis of Thin Truncated Cylinder Scatterers Using Incomplete Hankel Functions and Surface Impedance Boundary Conditions - Renato Cicchetti; Valentina Cicchetti; Antonio Faraone; Orlandino Testa (IEEE Access, 2020)
The incomplete Hankel functions (IHFs) are employed to evaluate the scattered field from thin truncated cylinders excited by uniform plane waves or by arbitrarily oriented elemental current sources. Metallic and dielectric lossy structures are modeled by means of impedance boundary conditions (IBCs) including surface curvature effects. The scattering currents, expanded in triangular basis functions, are determined upon solving electrical field integral equations (EFIEs) by means of the point-matching method of moments (MoM). The scattered field is then expressed in closed analytical form in terms of IHFs, thus yielding highly accurate numerical results. Furthermore, accurate IHFs approximants are also derived to reduce the computational burden in the analysis of large electrical structures. The proposed approach is demonstrated in practical applications involving cylindrical dielectric structures used in planar lenses, lossy dielectric cylinders suitable to model cane-like vegetation, as well as polarization rotators featuring multiple stages composed of thin metallic wire arrays.